Characterization of antimicrobial resistance mechanisms of multidrug resistant Gram negative bacterial wound infections and their clinical epidemiology from a tertiary care hospital in Karnataka, India - Gopinathan, Anusha; Mukhopadhyay, Chiranjay; K. E., Vandana (International Journal of Research in Medical Sciences, 2017)
Background: Extended spectrum beta lactamases, AmpC and Metallo-betalactamases in GNB isolates are a common occurrence in most Indian hospitals. The presence of these antimicrobial resistance mechanisms contributes to prolonged hospital stay, poor quality of life, increased morbidity and mortality among patients with these infections. The aim of the study was to analyse the antimicrobial resistance mechanisms of multidrug resistant Gram negative bacterial wound infection and their clinical epidemiology. Methods: A prospective study was conducted for one year among 100 patients of Kasturba Medical College, Manipal admitted with MDR GNB wound infections. The antibiogram and phenotypic resistance mechanisms of the bacterial isolate from these infections were identified using phenyl boronic acid and ethyl diacetate. The empirical therapy, specific therapy and clinical outcome of the patients were also analyzed. Results: Out of 100 study patients, 152 MDR GNB isolates were obtained. 73% patients were admitted in the surgical wards. 43% patients had diabetes. Ulcers (27%) and abscess (25%) were the most common diagnosis. Escherichia coli (39%), Klebsiella pneumoniae (24%) and Pseudomonas aeruginosa (19%) were the most common isolates. Maximum number of ESBL was seen among Enteric Gram negative bacilli (36%), MBL was seen among Pseudomonas aeruginosa and Acinetobacter species (55% each), AmpC was seen among enteric GNB (10%) and Acinetobacter species (18%). Cefaperazone sulbactam, amikacin and meropenem were the most common antibiotics given as specific therapy. Clinical response was observed among 93% patients. Conclusions: The determination of the antimicrobial resistance mechanisms of GNB isolates from wound infections plays a major role in establishing an antibiotic policy for the treatment of these infections.